Animal traction in Ghana - Houssou, Nazaire; Kolavalli, Shashidhara; Bobobee, Emmanuel; Owusu, Victor (International Food Policy Research Institute, 2013)
The recent interest of the government of Ghana in agricultural mechanization has largely focused on the provision of tractors and imported machinery to the farming population. Animal traction has not received much attention from the country’s policymakers. The strong demand for mechanization services (Houssou et al., 2012; Benin et al., 2012) and inadequate number of tractors to meet the demand in the country call for more effective use of other power sources for the agriculture sector. Using a survey of farmers who use draft animals and focus group discussions with farmers and key informants in the sector, this research examines the use of animal traction and analyses the major constraints to its widespread use in Northern Ghana.